Challenges in Diagnosis and Functional Assessment of Coronary Artery Disease in Patients With Severe Aortic Stenosis - Aleksandric, Srdjan; Banovic, Marko; Beleslin, Branko (Frontiers in Cardiovascular Medicine, 2022)
More than half of patients with severe aortic stenosis (AS) over 70 years old have coronary artery disease (CAD). Exertional angina is often present in AS-patients, even in the absence of significant CAD, as a result of oxygen supply/demand mismatch to the thickened myocardium due to the chronic increase of left ventricle (LV) afterload and increased wall stress, LV hypertrophy and wall thickening, and coronary microvascular dysfunction (CMD) which is defined as reduced coronary vasodilatory capacity below the ischemic threshold. Therefore, angina, as well as non-invasive stress tests, have a low both specificity and positive predictive value for the assessment of epicardial coronary stenosis severity in AS-patients. Moreover, in symptomatic patients with severe AS exercise testing is even contraindicated. Given the limitations of non-invasive stress tests, coronary angiography remains the standard examination for determining the presence and severity of CAD in AS-patients, although angiography alone has poor accuracy in the evaluation of its functional severity. To overcome this limitation, well-established invasive indices for the assessment of coronary stenosis severity, such as fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR), are now in focus, especially in the contemporary era with the rapid increment of transcatheter aortic valve replacement (TAVR) for the treatment of AS-patients. TAVR induces an immediate decrease in hyperemic microcirculatory resistance and a concomitant increase in hyperemic flow velocity, whereas resting coronary hemodynamics remains unaltered. These findings suggest that FFR may underestimate coronary stenosis severity in AS-patients, whereas iFR as the non-hyperemic index is independent of the AS severity. However, because resting coronary hemodynamics does not improve immediately after TAVR, the coronary vasodilatory capacity in AS-patients treated by TAVR remained impaired, and thus the iFR may overestimate coronary stenosis severity in these patients. The optimal method for evaluating myocardial ischemia in patients with AS and co-existing CAD has not yet been fully established, and this important issue is under further investigation. This review is focused on challenges, limitations, and future perspectives in the functional assessment of coronary stenosis severity in these patients, bearing in mind the complexity of coronary physiology in the presence of this valvular heart disease.